Kajian Folklor: Tembang Dolanan “E Dayohe Teko” Sebagai Refleksi Masalah Kehidupan - Desi Tri Utami; Muh Akbar Kurniawan (Journal on Education, 2025)
Reflection on life problems is a stage for exploring a human's actions and experiences in everyday life. This reflection process can be taken from various sources including tembang dolanan. The tembang dolanan "E Dayohe Teko" is a manifestation of Javanese cultural expression which has deep meaning in human life and society today. This research aims to (1) find out how the tembang dolanan "E Dayohe Teko" is a reflection of life problems, especially socio-economic dynamics (2) Tembang as a cultural communication tool (3) The relevance of the song to the lives of today's society. The research method used is context description with data collection techniques through literature study. The source of this research is the folk song "E Dayohe Teko" by Djoyoboyo. The theory used is Folklore studies. The results of this research show that the traditional song "E Dayohe Teko" is an example of Indonesia's cultural richness which is still relevant as a reflection on the problems of contemporary human life.